2016
DOI: 10.3109/14397595.2015.1123211
|View full text |Cite|
|
Sign up to set email alerts
|

Postmarketing surveillance of the safety and effectiveness of abatacept in Japanese patients with rheumatoid arthritis

Abstract: Objective: To perform a postmarketing surveillance study evaluating the safety and effectiveness of abatacept in Japanese patients with rheumatoid arthritis (RA). Methods: Safety and effectiveness data were collected for all RA patients (at 772 sites) treated with intravenous abatacept between September 2010 and June 2011. Patients were treated by the approved dosing regimen according to the package insert. Treatment effectiveness was evaluated at baseline and at weeks 4, 12, and 24 using Disease Activity Scor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

4
55
4

Year Published

2017
2017
2020
2020

Publication Types

Select...
6
1
1

Relationship

2
6

Authors

Journals

citations
Cited by 83 publications
(63 citation statements)
references
References 32 publications
(26 reference statements)
4
55
4
Order By: Relevance
“…Several studies have reported an association between bDMARD therapy and ILD events, although the mechanism underlying the relationship is unclear . PMS conducted by pharmaceutical companies in Japan reported a high incidence of ILD events in RA patients receiving etanercept (0.6% of 7091 patients), infliximab (0.5% of 5000 patients), adalimumab (0.6% of 3000 patients), tocilizumab (0.4% of 7901 patients), and abatacept (0.3% of 3985 patients) . Consistent with these previous studies, no significant difference in ILD events was seen among bDMARDs used in the present study (TNFi vs non‐TNFi).…”
Section: Discussionmentioning
confidence: 99%
“…Several studies have reported an association between bDMARD therapy and ILD events, although the mechanism underlying the relationship is unclear . PMS conducted by pharmaceutical companies in Japan reported a high incidence of ILD events in RA patients receiving etanercept (0.6% of 7091 patients), infliximab (0.5% of 5000 patients), adalimumab (0.6% of 3000 patients), tocilizumab (0.4% of 7901 patients), and abatacept (0.3% of 3985 patients) . Consistent with these previous studies, no significant difference in ILD events was seen among bDMARDs used in the present study (TNFi vs non‐TNFi).…”
Section: Discussionmentioning
confidence: 99%
“…Seven bDMARDs are currently approved in Japan for the treatment of RA and these drugs have different characteristics [1]. The results of postmarketing surveillance (PMS) that examined the safety and effectiveness of infliximab [2], etanercept [3][4][5], adalimumab (ADA) [6], tocilizumab (TCZ) [7,8] and abatacept [9] have been reported.…”
Section: Introductionmentioning
confidence: 99%
“…Previous studies have found only few factors that adequately predict the therapeutic response to ABA in RA treatment. These include CRP [29], presence or absence of MTX combination, history of use of other biologics [30], positivity for ACPA and RF [31], and age [32]. In this study, no significant correlation was observed between these known baseline patient characteristics and the proportion of peripheral blood Th17.1 cells.…”
Section: Discussionmentioning
confidence: 88%